Densely packed hybrid films comprising SnO2 and reduced graphite oxide for high-density electrochemical capacitors. Issue 41 (6th October 2016) - Byun, Segi; Shin, Byungha
Abstract : In this work, compact SnO2 /rGO hybrid film as a supercapacitor electrode has been fabricated using a simple solution-based two-step strategy. Abstract : A densely packed film of reduced graphite oxide (rGO) typically experiences restacking problems after thermal or chemical reduction processes. This can limit adsorption or diffusion of electrolyte ions inside the film to store electrical charges, thus impeding its energy storage ability. To solve this problem, we propose using sub-5 nm-diameter SnO2 nanoparticles (NPs) as spacers to prevent the restacking of the rGO film by the formation of a SnO2 /rGO heterostructure via a simple solution based two-step strategy. Compact rGO-based hybrid films, such as SnO2 /rGO, were created in the absence of any surfactants or polymers by using either a simple chemical redox reaction between graphene oxide (GO) and the SnCl2 precursor or by adjusting the amount of SnO2 NPs in the hybrids. Material and electrochemical characterizations reveal that only under certain experimental conditions, sensitive to the molar ratio of the SnCl2 precursor to GO, would the fabricated hybrid films have uniformly dispersed SnO2 NPs within the film and maintain a densely packed morphology with a high packing density of ca. 1.9 g cm −3 . Furthermore, because the uniform SnO2 NPs in the film act as effective spacers, the optimized hybrid film-based supercapacitor exhibits a remarkable enhancement of electrochemical performances, including high volumetric capacitances in both acidic and neutral electrolytes, superior rate performance, and long-term stability.